2022
DOI: 10.1186/s12913-022-07763-3
|View full text |Cite
|
Sign up to set email alerts
|

Unprofessional behaviours experienced by hospital staff: qualitative analysis of narrative comments in a longitudinal survey across seven hospitals in Australia

Abstract: Background Unprofessional behaviours of healthcare staff have negative impacts on organisational outcomes, patient safety and staff well-being. The objective of this study was to undertake a qualitative analysis of narrative responses from the Longitudinal Investigation of Negative Behaviours survey (LION), to develop a comprehensive understanding of hospital staff experiences of unprofessional behaviours and their impact on staff and patients. The LION survey identified staff experiences and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…The consequences of these behaviours on the well‐being of individuals are substantial 3–5 . Evidence is also emerging of the effects on quality of care and patient outcomes 6 .…”
Section: Increased N (Col %) Did Not Change N (Col %) Decreased N (Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of these behaviours on the well‐being of individuals are substantial 3–5 . Evidence is also emerging of the effects on quality of care and patient outcomes 6 .…”
Section: Increased N (Col %) Did Not Change N (Col %) Decreased N (Co...mentioning
confidence: 99%
“…3 The consequences of these behaviours on the well-being of individuals are substantial. [3][4][5] Evidence is also emerging of the effects on quality of care and patient outcomes. 6 Multiple simulation studies in different countries have shown that clinical teams and individuals exposed to unprofessional behaviours perform significantly worse on a range of metrics, from diagnostic performance to clinical vigilance.…”
mentioning
confidence: 99%
“…Nurses' QWL is defined as “the degree to which registered nurses are able to satisfy important personal needs through their experiences in their work organization while achieving the organization's goals” [5] . QWL posits that people are the most critical resource in an organization and should be treated with dignity and respect [6] , [7] . QWL focuses on workplace improvement based on a dual agenda of employee well-being and organizational performance [6] .…”
Section: Introductionmentioning
confidence: 99%
“…QWL posits that people are the most critical resource in an organization and should be treated with dignity and respect [6] , [7] . QWL focuses on workplace improvement based on a dual agenda of employee well-being and organizational performance [6] . An improved QWL is essential to recruit and retain nurses, increase their productivity and organizational commitment, enhance effectiveness of the patient care system and ensure greater patient satisfaction [8] [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation